Beyond the androgen receptor: New approaches to treating metastatic prostate cancer. Report of the 2013 Prouts Neck Prostate Cancer Meeting. Issue 3 (February 2014) - Pienta, Kenneth J.; Walia, Guneet; Simons, Jonathan W.; Soule, Howard R.
<x xml:space="preserve">Abstract</x> INTRODUCTION The Prouts Neck Meetings on Prostate Cancer began in 1985 through the efforts of the Organ Systems Branch of the National Cancer Institute to stimulate new research and focused around specific questions in prostate tumorigenesis and therapy. METHODS These meetings were think tanks, composed of around 75 individuals, and divided equally between young investigators and senior investigators. Over the years, many new concepts related to prostate cancer resulted from these meetings and the prostate cancer community has sorely missed them since the last one in 2007. RESULTS We report here the first of a new series of meetings. The 2013 meeting focused on defining how the field of treatment for metastatic prostate cancer needs to evolve to impact survival and was entitled: "Beyond AR: New Approaches to Treating Metastatic Prostate Cancer." As castrate resistant prostate cancers escape second generation anti‐androgen agents, three phenotypes/genotypes of CRPC appear to be increasing in prevalence and remain resistant to treatment: NeuroEndocrine Prostate Cancer, Persistent AR—Dependent Prostate Cancer, and Androgen Receptor Pathway Independent Prostate Cancer. DISCUSSION It is clear that new treatment paradigms need to be developed for this diverse group of diseases. The Prouts Neck 2013 Meeting on Prostate Cancer helped to frame the current state of the field and jumpstart ideas for new avenues of treatment. Prostate 74:314–320, 2014. © 2013 Wiley Periodicals, Inc.